Implementing Nazhoriyah Al-Wahdah in Arabic Language Learning: A Qualitative Study on Student Response and Implications - Ahmad Ghozin, Amrul Haq; Khizanatul , Hikmah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the implementation of Nazhoriyah Al-Wahdah system and student response in Arabic language learning. A qualitative research design was employed, utilizing data collection techniques such as observation, interviews, questionnaires, and documentation. The data analysis followed Miles and Huberman's techniques, involving data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Nazhoriyah Al-Wahdah in Arabic language learning commenced with lesson planning, combining content from Durusullughoh textbook (Pondok Modern Darussalam Gontor) and Silsilah Ta'lim Al-Lughah Al-Arobiyyah (LIPIA). The learning process encompassed three stages: listening and writing skills, reading comprehension, and conversational skills. Summative assessments were conducted at the end of each semester, with evaluation content derived from Durusullughoh. Student responses indicated a positive perception and enthusiasm in mastering various Arabic language skills through the implementation of Nazhoriyah Al-Wahdah. The study implies the need to further enhance practical Arabic language usage in daily life, guided directly by instructors. This research contributes to the field of Arabic language education and encourages future investigations on the effectiveness and broader implementation of Nazhoriyah Al-Wahdah system in diverse educational contexts. Highlight: Implementation of Nazhoriyah Al-Wahdah in Arabic language learning combines content from reputable textbooks. The three-stage approach in implementing Nazhoriyah Al-Wahdah: listening and writing, reading comprehension, and conversation. Positive student response indicates ease in understanding and enthusiasm for mastering Arabic language skills. Keyword: Nazhoriyah Al-Wahdah, Arabic Language Learning, Student Response, Qualitative Research, Implementation